DIPLOMASI MARITIM INDONESIA DALAM KASUS ILLEGAL FISHING VIETNAM DI LAUT NATUNA PERIODE 2014-2019 - Kenny Firdaus Tarigan, (2022)
This study discusses Indonesian Maritime Diplomacy in Vietnam's Illegal Fishing Case in the Natuna Sea for the 2014-2019 Period. Illegal Fishing activities or activities that are carried out contrary to the applicable fisheries law are the definition of Illegal Fishing or Illegal Fishing. Vietnam is the main actor in Illegal Fishing activities in the Natuna Sea. This study raises the research question "How is maritime diplomacy carried out by Indonesia against Vietnam in order to overcome Illegal Fishing crimes in the Natuna Region for the 2014-2019 period?". To answer these questions, this study uses theories and concepts including: diplomacy and maritime diplomacy. The method in this study uses a descriptive qualitative method which emphasizes the exploration and clarification of a phenomenon or social reality by describing a number of variables relating to the problem and unit being studied. According to research results, Indonesia through maritime diplomacy with Vietnam has succeeded in reducing the activities of foreign fishermen from Vietnam who commit Illegal Fishing crimes.